The Role of Crowdfunding in Poverty Alleviation: A Literature Review - Ammaria, Syarafina Wahyu; Kusuma, Chico; Zahiyah, Naurah Nur; Rofidah, Alif (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Crowdfunding is an innovative approach that uses the internet to raise funds, providing potential social financing to help alleviate poverty, especially amid limited access to formal capital. This study aims to identify, analyze, and synthesize evaluative models used to assess the effectiveness of crowdfunding in the context of supporting poverty alleviation efforts. The approach used is a literature review based on the PRISMA method. Out of 200 articles, seven were selected for detailed analysis. The research findings indicate that the success of crowdfunding depends on the synergy between technological aspects—such as transparency, efficiency, and accessibility—and social aspects, including community participation, emotional narratives, and public trust. Crowdfunding has proven to bridge the financing access gap for disadvantaged groups, strengthen social solidarity, and enhance financial inclusion, particularly through the sharia model in Indonesia. However, issues such as uneven distribution of funds, low financial literacy, and the threat of fraud remain challenges that must be addressed by strengthening regulations and verification systems. Therefore, the integration of technology and community empowerment is a crucial factor in maximizing the role of crowdfunding as a sustainable strategy to address poverty in the digital age.